2023
DOI: 10.1101/2023.03.21.533648
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The value of time in the invigoration of human movements when interacting with a robotic exoskeleton

Abstract: Time and effort are critical factors that are thought to be subjectively balanced during the planning of goal-directed actions, thereby setting the vigor of volitional movements. Theoretical models predicted that the value of time should then amount to relatively high levels of effort. However, the time-effort tradeoff has so far only been studied for a narrow range of efforts. Therefore, the extent to which humans can invest in a time-saving effort remains largely unknown. To address this issue, we used a rob… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 88 publications
(141 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it is an interesting observation when coupled with the limited effects reported on kinematics because of their potential implications. Indeed, recent works have shown that humans are prone to expending large amounts of energy to save time [57], which was also shown while interacting with an exoskeleton [58]. Such an energetic expenditure was as predicted by the minimum time-effort theory in the field of human motor control [59,60], which is probably due to a temporal discounting of the reward (here, achieving the task) associated with the movement [61,62].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, it is an interesting observation when coupled with the limited effects reported on kinematics because of their potential implications. Indeed, recent works have shown that humans are prone to expending large amounts of energy to save time [57], which was also shown while interacting with an exoskeleton [58]. Such an energetic expenditure was as predicted by the minimum time-effort theory in the field of human motor control [59,60], which is probably due to a temporal discounting of the reward (here, achieving the task) associated with the movement [61,62].…”
Section: Discussionmentioning
confidence: 86%
“…Furthermore, it mainly introduces one large JM that can be efficiently identified following a simple procedure [50]. Finally, the proposed design seems to be suitable for clinical interventions or work tasks and for the burgeoning field of human movement studies involving exoskeletons [51,58,68]. In future works, the inclusion of passive degrees of freedom at the arm interface will be performed on the basis of the present study to further minimize unwanted interaction efforts while implementing a relatively simple design.…”
Section: Discussionmentioning
confidence: 99%